Radial distribution of electrons rotation moment in hall effect and plasma-ion thrusters - Guo, Zongshuai (Avìacìjno-kosmìčna tehnìka ì tehnologìâ, 2021)
The subject matter of the article is the radial distribution of electrons movement parameters inside electric propulsion thrusters with closed electrons drift. The radial magnetic field in Hall effect thrusters is the limits the axial flow of electrons because of interaction with azimuth electron current. In turn, this azimuth current exists as a result of rivalry between the attempt of the magnetic field to transform electrons current completely closed one and the loss of electrons rotation moment in collisions. Similar processes take place in the ionization chamber of plasma-ion thrusters with the radial magnetic field. The attempts to estimate electrons parameters through only collisions with ions and atoms inside volume have given the value of axial electrons current much lower than really being. This phenomenon is called anomalous electrons conductivity, which was tried to be explained as a consequence of various effects including "near-the-wall-conductivity", which was explained as a result of non-mirror reflection of electrons from the Langmuir layer near the walls of the thruster channel. The disadvantage of this name is the fact that the reflection of the electron occurs before reaching the surface from the potential barrier at the plasma boundary with any environment: the wall, but also with the environment vacuum. The potential distribution in the Langmuir layer is non-stationary and inhomogeneous due to the presence of so-called plasma oscillations. The definition of "conductivity" is just as unfortunate in this name, because the collisions are always not a factor of conductivity, but on the contrary – of resistance. The goal is to solve the task of electrons rotation moment distribution in the thruster channel. The methods used are the formulation of the kinetic equation for electrons distribution function over the velocities, radius, and projections of the coordinates of the instantaneous center of cyclotron rotation; solution of this equation and finding with its use the distribution of the gas-dynamic parameters of electrons along the cross-section of the channel. Conclusions. A mathematical model of electrons rotation moment dynamics is proposed, which allows using plasma-dynamics equations to analyze its distribution along the cross-section of thruster channel and to estimate the effect of "near-the-wall-conductivity" using appropriate boundary conditions.